A socialização do conhecimento em finanças pessoais - Silva, Alessandra de Almeida (2024)
The present study has the general objective of understanding the socialization of knowledge in personal finance. The specific objectives are to: (i) understand the elements related to financial education and personal finance through a meta-synthesis; (ii) highlight how the primary socialization of knowledge in personal finance occurs; (iii) understafind how secondary socialization related to personal financial knowledge takes place in public and private educational institutions in the state of Paraná. To achieve these objectives, the study was conducted in three stages: the first stage involved a meta-synthesis based on the analysis of qualitative case studies to understand the elements related to personal financial education; the second and third stages involved interviews to identify empirical evidence through a qualitative approach. Regarding data analysis, this study adopted first- and second-order analysis, according to Gioia et al. (2013), which revealed the dimensions and sub-dimensions related to the primary and secondary socialization of personal financial knowledge. The research participants included ten teachers and twelve students from public and private schools in the state of Paraná, who had contact with finance-related subjects. From the analyses, the elements responsible for personal financial education were identified, emphasizing public policy programs, teaching methodologies and pedagogical elements, awareness of behavior, social norms, and religious precepts that encourage the development of social and financial responsibility in individuals, which are the responsibility of stakeholders involved in the financial education process. This study presents as a theoretical contribution the exposition of the main actions, intentions, and stakeholders responsible for financial education in society; the understanding of the main norms, values, and behaviors related to the primary socialization of financial knowledge; and the identification of key concepts, teaching methodologies and pedagogical elements, social practices and discourses, and formal and informal educational institutions responsible for the secondary socialization of financial knowledge. As practical implications, the study suggests actions and policies to improve the achievement of financial education goals for the population; emphasizes the importance of understanding the social role of caregivers as transmitters of personal financial knowledge during primary socialization; and presents the role of public policies in building a school curriculum that meets the learning needs and socioeconomic contexts of students.